Association Between Diabetes and COVID-19: A Retrospective Observational Study With a Large Sample of 1,880 Cases in Leishenshan Hospital, Wuhan - Liu, Zeming; Li, Jinpeng; Huang, Jianglong; Guo, Liang; Gao, Rongfen; Luo, Kuan; Zeng, Guang; Zhang, Tingbao; Yi, Meilin; Huang, Yihui; Chen, Jincao; Yang, Yibin; et al. (Frontiers in Endocrinology, 2020)
Aims: This study aimed to investigate the clinical courses and outcomes of diabetes mellitus patients with coronavirus disease 2019 (COVID-19) in Wuhan. Methods: This study enrolled 1880 consecutive patients with confirmed COVID-19 in Leishenshan Hospital. We collected and analyzed their data, including demographic data, history of comorbidity, clinical symptoms, laboratory tests, chest computed tomography (CT) images, treatment options, and survival. Results: The percentages of patients with diabetes among the severe and critical COVID-19 cases were higher than those among the mild or general cases (89.2%, 10.8% vs. 0%, p=0.001). However, patients with and without diabetes showed no difference in the follow-up period (p=0.993). The mortality rate in patients with or without diabetes was 2.9% (n=4) and 1.1% (n=9), respectively (p=0.114). Univariate and multivariate Cox regression analyses and the Kaplan-Meier curves did not show any statistically significant differences between patients with and without diabetes (all p values > 0.05). Conclusions: Our study results suggested that diabetes had no effect on the prognosis of COVID-19 patients but had a negative association with their clinical courses. These results may be useful for clinicians in the management of diabetic patients with COVID-19.